2014
DOI: 10.1093/brain/awu137
|View full text |Cite
|
Sign up to set email alerts
|

Brain differences between persistent and remitted attention deficit hyperactivity disorder

Abstract: Previous resting state studies examining the brain basis of attention deficit hyperactivity disorder have not distinguished between patients who persist versus those who remit from the diagnosis as adults. To characterize the neurobiological differences and similarities of persistence and remittance, we performed resting state functional magnetic resonance imaging in individuals who had been longitudinally and uniformly characterized as having or not having attention deficit hyperactivity disorder in childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 38 publications
9
61
1
Order By: Relevance
“…Our results are also in accord with previous resting-state fMRI studies showing stimulant-induced functional segregation between default and salience networks (Sripada et al 2013). Consistent with the default network dysregulation hypothesis of ADHD (Mattfeld et al 2014), decreased synchronization between these networks may represent decreased interference by default network processes in task-positive operations.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in accord with previous resting-state fMRI studies showing stimulant-induced functional segregation between default and salience networks (Sripada et al 2013). Consistent with the default network dysregulation hypothesis of ADHD (Mattfeld et al 2014), decreased synchronization between these networks may represent decreased interference by default network processes in task-positive operations.…”
Section: Discussionsupporting
confidence: 92%
“…A study in adults with a childhood diagnosis of ADHD reported that persistent ADHD was associated with reduced connectivity within the DMN (medial PFC and PCC) compared with both controls and remitted ADHD, which did not differ ( Figure 3). 6 However, the expected negative connectivity (anticorrelation) between the dlPFC and medial PFC was present in the control group, but not in either the persistent or remitted ADHD groups. The authors of this study suggested this may indicate executive functioning weakness, as the ADHD groups were similarly impaired on neuropsychological testing.…”
Section: Neurobiologymentioning
confidence: 90%
“…The authors of this study suggested this may indicate executive functioning weakness, as the ADHD groups were similarly impaired on neuropsychological testing. 6 Another study that included two groups of medication naïve adults with ADHD reported increased connectivity between the DMN and a small region within left lateral PFC based on independent component analysis ( Figure 3). 7 In addition, higher levels of resting state activity within that area of PFC were associated with lower levels of performance on an attentional tasks.…”
Section: Neurobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the way to confront the creative task, there are similarities of functioning between ADHD and creative, both groups show difficulties for the deactivation of the default neural network (DNN) to tasks that require more mental effort, which leads to the maintenance of a dispersed, unfocused mental state (Mattfeld et al, 2014, Sonuga-Barke & Castellanos, 2007, Uddin et al, 2008.…”
Section: Neurological Hypothesismentioning
confidence: 99%